Parthenolide Suppresses T Helper 17 and Alleviates Experimental Autoimmune Encephalomyelitis - Zhang, Zhihui; Zhang, Kai; Zhang, Mi; Zhang, Xiaomin; Zhang, Rongxin (Frontiers in Immunology, 2022)
T helper (Th) cells play crucial roles in inflammation and adaptive immune system. Importantly, Th17 cells, a major pathogenic Th cell subset, are involved in the pathogenesis of multiple sclerosis (MS) and its classical animal modal experimental autoimmune encephalomyelitis (EAE). Previous studies have shown that Parthenolide (PTL), a sesquiterpene lactone, possesses potent anti-cancer and anti-inflammatory activities. However, the immunosuppressive effect of PTL on the pathogenic Th17 cell and MS is unclear. In this study, we showed that PTL treated could alleviate clinical symptoms by inhibiting inflammatory cell infiltration, reducing inflammation and demyelination of CNS. In addition, the mRNA expression of cytokines and inflammatory factors in CD4+ T cell, especially Th1 and Th17 cells, reduced in both CNS and peripheral immune tissue of EAE mice. Furthermore, PTL could inhibit the reactivation of MOG-specific T cells and the differentiation of naïve CD4+ T cells into Th17 cells in vitro. We also found that PTL inhibited nuclear factor kappa B (NF-κB) signaling and retinoid-related orphan receptor-γt (RORγt) in mouse Th17 cell and human jurkat cell line. Taken together, our data demonstrated a critical immune-suppressive effect of PTL on autoimmune inflammation through regulating Th17 cells and NF-κB/ RORγt pathway.